Status of the AMANDA experiment - Andrés,E; Askebjer,P; Barwick,SW; Bay,R; Bergström,L; Bouchta,A; Biron,A; Carius,S; Costa,C; Cowen,D; Dalberg,E; Ekström,P; et al. (Nuclear Physics B Proceedings Supplements, 1999)
The AMANDA high energy neutrino telescope has successfully been increased in size from four detector strings to ten detector strings during the 1996/1997 season. The first upward going muon-neutrino candidates have been reconstructed from the 1996 year's four-string data. Three new detector strings will be deployed during 1997/1998 to 2350 metres depth.